Land use management solutions in response to climate change: Case study in the central coastal areas of Vietnam - Phuong Tran Trong; Vien Tran Duc (Open Agriculture)
Vietnam is highly susceptible to climate change, which has significantly affected its agricultural production. Therefore, sustainable land use that adapts to climate change is a crucial research topic. This study was conducted in Loc Ha district, Ha Tinh province in central Vietnam, an area particularly vulnerable to climate change. The results indicate an increasing trend in temperature and rainfall, with flooding being the primary impact of climate change on agriculture, while drought has a moderate impact. This study assessed the suitability of land in the Loc Ha district to facilitate land use planning in line with climate change conditions until 2035. The land suitability analysis in Loc Ha district reveals that the district has 12 soil types across 8 soil groups, divided into 55 land units with varying characteristics. Adapting land use management to the climate change situation is an effective solution for agricultural development in the research area and across Vietnam in the future.